A CLASS OF THIRD ORDER MULTI-POINT BOUNDARY VALUE PROBLEM - Du, Zengji; 杜增吉; Cai, Guolan; 蔡果藍; Ge, Weigao; 葛渭高 (Taiwanese journal of mathematics, 2005)
This paper deals with a class of third order multi-point boundary value problem at resonance case. Some existence theorems are obtained by using the coincidence degree theory of Mawhin.